Observation of tungsten impurities induced 2/1 snake fluctuations and their interactions with discrete double BAE pairs on EAST. (1st November 2018) - Xu, Ming; Zhou, T.; Xu, L.Q.; Hu, L.Q.; Duan, Y.M.; Liu, Y.; Zhang, L.; Shi, T.H.; Li, Y.Y.; Lyu, B.; Zhao, H.L.; Chen, Y.J.; et al.
Abstract: The snake perturbations around q = 2 surface with strong poloidal asymmetry are frequently observed on EAST after the injection of high-Z impurities. A new pair of Beta-induced Alfvén eigenmodes (BAEs) with lower frequencies also come along with the 2/1 snake fluctuations, in addition to the conventional BAE pair that accompany the pure 2/1 tearing modes (TMs) on EAST, which have already been investigated (Xu et al 2013 Plasma Phys. Control. Fusion 55 065002). The radial structures of the intensities of the snake perturbations and the two BAE pairs are mapped out for the first time, indicating that these BAE quartet are discrete modes over the radial extension and are situated slightly outside the annulus of TM activities but centered at slightly different positions. The constant frequency spectra of the BAEs are explained as the eigen-solutions of the radial differential equation for the global modes, and the rich multiplicity of BAEs is attributed to various levels of BAE continuum splittings when more detailed physics are taken into consideration.